Effect of surgical experience on the macroscopic diagnosis of appendicitis: A retrospective cohort study. (April 2015) - Pham, Helen; Devadas, Michael; Howle, Julie
Abstract: Background: We aimed to determine whether intraoperative macroscopic assessment of the appendix improves with surgical experience and whether the accuracy of the intraoperative assessment of the appendix is different in respect to sex of the patient. Methods: Medical records of all appendicectomies performed during an 18-month period (2011–2012) at Westmead Hospital, Australia were reviewed. Accuracy of intraoperative macroscopic description correlating to histopathology was compared between groups based on the training level of the surgeon. Results: Correlation between the intraoperative diagnosis and final histopathology result was 83.5% of the 303 cases. The diagnostic accuracy amongst junior trainees, senior trainees and consultants did not differ with accuracy rates of 85%, 81.6% and 88.2% respectively, (P = 0.44). The false negative rate was higher in females than in males (19.1% versus 7.2%; P = 0.007). Conclusions: Our findings demonstrated that operator experience does not affect the accuracy of the intraoperative assessment of appendixes. We recommend that an appendicectomy be performed when clinically indicated regardless of macroscopic appearance. Highlights: We examined the accuracy of intraoperative macroscopic assessment of the appendix in correlation to the experience of the operator. The diagnostic accuracy amongst junior trainees, senior trainees and consultants did not differ with accuracy rates. The false negative rate was higher in females than in males (19.1% versus 7.2%; P = 0.007). The false positive rate was higher in males than in female patients (43.3% versus 22.2%; P = 0.05). We recommend that an appendicectomy be performed when clinically indicated regardless of macroscopic appearance.